Immunoendocrine Peripheral Effects Induced by Atypical Antipsychotics - Alvarez-Herrera, Samantha; Escamilla, Raúl; Medina-Contreras, Oscar; Saracco, Ricardo; Flores, Yvonne; Hurtado-Alvarado, Gabriela; Maldonado-García, José Luis; Becerril-Villanueva, Enrique; Pérez-Sánchez, Gilberto; Pavón, Lenin (Frontiers in Endocrinology, 2020)
Atypical antipsychotics (AAP) or second-generation antipsychotics are the clinical option for schizophrenia treatment during acute psychoses, but they are also indicated for maintenance during lifetime, even though they are being used for other psychiatric conditions in clinical practice such as affective disorders and autism spectrum disorder, among others. These drugs are differentiated from typical antipsychotics (TAP) based on their clinical profile and are a better choice because they cause fewer side effects regarding extrapyramidal symptoms (EPS). Even though they provide clear therapeutic benefits, AAP induce peripheral effects that trigger phenotypic, functional, and systemic changes outside the Central Nervous System (CNS). Metabolic disease is frequently associated with AAP and significantly impacts the patient’s quality of life. However, other peripheral changes of clinical relevance are present during AAP treatment, such as alterations in the immune and endocrine systems as well as the intestinal microbiome. These less studied alterations also have a significant impact in the patient's health status. This manuscript aims to revise the peripheral immunological, endocrine, and intestinal microbiome changes induced by AAP consumption recommended in the clinical guidelines for schizophrenia and other psychiatric disorders.